EXPLORING STUDENTS’ AND LECTURERS’ ANXIETY IN LEARNING ENGLISH DURING EMERGENCY REMOTE TEACHING IN A PUBLIC UNIVERSITY IN NORTH BALI - Santosa, Made Hery; Wulandari, Ni Luh Putu Novi; Mahendrayana, Gede (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
This study aimed to investigate students' and lecturers’ anxiety in learning English during emergency remote teaching in a public university in North Bali. This study was formed in a quantitative study. The data were collected by doing a survey and giving the questionnaire that was developed based on the FLCAS (Foreign Language Classroom Anxiety Scale) for the participants. There were 200 university students and 9 lecturers of English Language Education in the research setting as the participants. The study found that the university students’ level was mildly anxious or indicated a moderate level of anxiety. Meanwhile, the lecturers’ anxiety level was very relaxed or indicated as low anxiety level. From the results, it can be concluded that most of university students did not feel afraid and happy. Meanwhile, the lecturers felt joy in teaching and learning English during the emergency remote teaching.